Meta Analysis: Effect of Oral Contraceptives on Obesity in Fertile Age Women in Asia - Ulhaq, Muhammad Zia; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Obesity is a disease with a com